1979
DOI: 10.1017/s0140525x00063949
|View full text |Cite
|
Sign up to set email alerts
|

Précis of O'Keefe & Nadel'sThe hippocampus as a cognitive map

Abstract: Theories of spatial cognition are derived from many sources. Psychologists are concerned with determining the features of the mind which, in combination with external inputs, produce our spatialized experience. A review of philosophical and other approaches has convinced us that the brain must come equipped to impose a three-dimensional Euclidean framework on experience – our analysis suggests that object re-identification may require such a framework. We identify this absolute, nonegocentric, spatial framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
522
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(551 citation statements)
references
References 169 publications
25
522
1
3
Order By: Relevance
“…As a rat explores a spatial environment, CA1 and CA3 neurons fire selectively when the animal occupies particular locations within the environment. These 'place cells' are believed to reflect elements of a cognitive map of the environment [75] or representations of places where significant events occur within episodic memories [76,77]. Characterization of age-associated changes in the firing patterns of place cells might shed light on disturbances in memory processing in the aged hippocampus.…”
Section: Information Processing By Hippocampal Place Cells Of Aged Anmentioning
confidence: 99%
“…As a rat explores a spatial environment, CA1 and CA3 neurons fire selectively when the animal occupies particular locations within the environment. These 'place cells' are believed to reflect elements of a cognitive map of the environment [75] or representations of places where significant events occur within episodic memories [76,77]. Characterization of age-associated changes in the firing patterns of place cells might shed light on disturbances in memory processing in the aged hippocampus.…”
Section: Information Processing By Hippocampal Place Cells Of Aged Anmentioning
confidence: 99%
“…A large proportion of hippocampal neurons (place cells) are known to selectively discharge as animals traverse circumscribed portions of environmental space, referred to as place fields (24,25). Hill and Best (11) showed that place fields emerge relatively quickly when placed in a new environment.…”
mentioning
confidence: 99%
“…This is clearly an allocentric strategy, and has been the subject of detailed research in neuroscience (O'Keefe & Nadel, 1979). This strategy is important when we try to plan a route, among the many possible.…”
Section: Cognitive Strategies For Spatial Navigationmentioning
confidence: 99%